Unusual vasomotor coronary arterial responses after reversal of ergonovine induced spasm with glyceryl trinitrate. Issue 3 (March 1984) - Hattori, R; Takatsu, Y; Yui, Y; Nonogi, H; Kawai, C
Abstract : Unusual vasomotor responses in the coronary arteries occurred in two patients after the administration of glyceryl trinitrate to relieve spasm induced by ergonovine maleate. In one patient after treatment with glyceryl trinitrate and despite dilatation of the adjoining segments a new severe reduction in diameter occurred distally to the segments of the right coronary artery where the ergonovine induced spasm developed. In the other patient the left anterior descending artery filled very slowly after the completely occlusive spasm of the right coronary artery had resolved with glyceryl trinitrate though the circumflex did not. These vasomotor changes were associated with chest discomfort and electrocardiographic abnormalities in both cases. These findings indicate that caution is needed when performing provocative tests even after the ergonovine induced spasm has been reversed with glyceryl trinitrate.